Karl Barth on faith: a systematic exploration - Watson, Brandon K. (Theologische Bibliothek Töpelmann, 2024)
"The present volume examines an underdeveloped doctrinal component in the theology of Karl Barth. Closely examining Barth's theological development of the concept of faith, the work argues for a necessary conceptual grounding of faith in divine ontology. Key doctrines in Barth's corpus are systematically examined as they relate to formulating a hermeneutic of faith." --
Keywords: Barth, Karl -- 1886-1968; Hochschulschrift; Glaube; Auserwählung; Barth, Karl; Dialektische Theologie; Christologie; Pneumatologie; Ontologie; Theologische Erkenntnistheorie